2010
DOI: 10.1186/1752-4458-4-26
|View full text |Cite
|
Sign up to set email alerts
|

Public perception of mental health in Iraq

Abstract: BackgroundPeople who suffer from mental illness, the professionals who treat them, and indeed the actual concept of mental illness are all stigmatised in public perception and often receive very negative publicity. This paper looks at Iraq, which has a population of 30 million who are mainly Moslem. Mental health services and professionals have historically been sparse in Iraq with 1 psychiatrist per 300,000 before 2003 falling to 1 per million until recently and 1 primary care centre (40 Healthcare Workers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
85
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 17 publications
12
85
1
Order By: Relevance
“…This study is in line with the study conducted in India where 39.4% of the respondents were found to have poor perception about mental illness [14]. But it is not consistent with study done in Iraq where 30% of the respondents were with poor perception of mental illness [13]. The variation might be due to socioeconomic and cultural difference among respondents.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This study is in line with the study conducted in India where 39.4% of the respondents were found to have poor perception about mental illness [14]. But it is not consistent with study done in Iraq where 30% of the respondents were with poor perception of mental illness [13]. The variation might be due to socioeconomic and cultural difference among respondents.…”
Section: Discussionsupporting
confidence: 72%
“…Also in study done in Iraq and India no significant association was found with age regarding the community's view of mental illness. This could be due to the tool used or sample characteristics as rural and urban community are involved in both studies [13, 14]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most prevalent belief about mental health among older adults was that individuals are accountable for their mental illness. Furthermore, SADIK, BRADLEY, AL-HASOON and JENKINS (2010) reported that in developing countries, although the aetiology of mental illness was understood, it was demonstrated that understanding the nature of mental illness is less prevalent, consequently resulting in negative attitudes and stigma. Nevertheless, individuals who are required to have a large amount of mental health knowledge such as general practitioners, continued to demonstrate negative stigma towards diagnosed patients (HANSSON et al 2013).…”
Section: Knowledge and Its Effect On Decreasing Stigmamentioning
confidence: 99%